Peran Otoritas Jasa Keuangan Daerah Istimewa Yogyakarta dalam Mediasi Sengketa Sektor Jasa Keuangan - Kaffi, Muhammad Kaffi Al Mubaarok; Sahril Fadli (Majelis: Jurnal Hukum Indonesia, 2025)
The complexity of the financial services sector necessitates effective dispute resolution mechanisms. This study analyzes the implementation of financial services dispute mediation by OJK DIY under OJK Regulation No. 1/LAPS-SJK/I/2021 and explores procedural constraints. An empirical juridical method with qualitative approach was employed through in-depth interviews with OJK DIY officials and consumers utilizing mediation services, supplemented by secondary data from official documents and related regulations analyzed descriptively. Findings reveal a low mediation success rate of 18.67% from 2,501 complaints in 2023 with an average resolution duration of 10 working days. Primary obstacles include digital gaps in service access, insufficient legal and financial literacy among the public, bargaining power disparities between consumers and financial institutions, and limited program socialization. The research recommends transforming OJK DIY's mediation system through enhanced digital access, strengthened consumer education, equalized bargaining positions, and intensified socialization. This study contributes to developing more efficient and equitable dispute resolution policies and provides strategic recommendations for improving consumer protection in Indonesia's financial services sector.